Hydrogen in low-carbon energy systems in Japan by 2050: The uncertainties of technology development and implementation. (27th September 2018) - Ozawa, Akito; Kudoh, Yuki; Murata, Akinobu; Honda, Tomonori; Saita, Itoko; Takagi, Hideyuki
Abstract: Low-carbon technologies will play a vital role in the realization of environmentally sustainable economies. However, uncertainties remain as to the feasibility of their development and implementation. Therefore, possible scenarios for the potential of these technologies should be considered to allow for flexible decision-making with respect to long-term energy strategies in Japan. This study evaluates the role of hydrogen in future energy systems in Japan using a MARKet ALlocation (MARKAL) model. A range of uncertainties are considered for nuclear power generation and carbon capture and storage (CCS) from fossil power generation. Our results suggest that an 80% reduction of CO2 emissions from the 2013 level by 2050 requires emissions from the electricity sector to decrease to nearly zero. Hydrogen power must play a functional role in future energy systems in Japan, but its contribution should depend on nuclear power and CCS. Highlights: The feasibility of low-carbon technologies in energy systems remains uncertain. A MARKAL model was used to evaluate technological uncertainties under scenarios. CO2 emissions from the electricity sector must be reduced to nearly zero by 2050. Hydrogen should play a key role in future power generation in Japan. Nuclear energy and CCS should determine hydrogen contributions to energy systems.